Umbilical Cord Mesenchymal Stem Cells Ameliorate Kidney Injury in MRL/Ipr Mice Through the TGF-β1 Pathway - Huang, Chunkai; Meng, Mingyao; Li, Shuo; Liu, Shiyuan; Li, Lin; Su, Yanjun; Gao, Hui; He, Shan; Zhao, Yiyi; Zhang, Min; Hou, Zongliu; Wang, Wenju; et al. (Frontiers in Cell and Developmental Biology, 2022)
In this study, we investigated the therapeutic effects and mechanism of umbilical cord mesenchymal stem cells (UC-MSCs) in MRL/Ipr mice. UC-MSCs, methylprednisolone (MP), and their combination were used to treat MRL/Ipr mice. The therapeutic effects were evaluated by renal function assessment, and renal tissues were HE, PAS, and Masson staining and electron microscopy. Subsequently, podocyte injury was detected by podocin in renal tissue by immunofluorescence. To further explore the mechanism, serum TGF-β1 was measured, and TGF-β1, p-Smad3, TRAF6 in renal tissue were detected by western blotting. In vitro, TGF-β1 were used to stimulate podocytes, the podocyte activity and changes in synaptopodin were observed after UC-MSC treatment. Significant improvements in renal function and pathological injury were observed in UC-MSC group than in lupus nephritis (LN) model group. UC-MSC and MP treatment improved podocyte injury in MRL/Ipr mice. Western blot examination of renal tissues indicated that TGF-β1, p-Smad3 and TRAF6 expression levels in the LN model group were significantly increased, and UC-MSC treatment showed that the expression levels of these proteins in the kidney were significantly decreased. After TGF-β1 stimulation in vitro, podocyte activity decreased, and UC-MSC treatment improved podocyte activity and restored synaptopodin expression. In Conclusion，UC-MSC therapy could improve the deterioration of renal function and the pathological changes of renal tissues in MRL/Ipr mice. Our study suggested that UC-MSCs may improve kidney injury and podocyte injury in LN mice by inhibiting the TGF-β1 pathway.